2008
DOI: 10.1111/1524-4725.2006.32001
|View full text |Cite
|
Sign up to set email alerts
|

Variable-Pulse Nd:YAG Laser in the Treatment of Facial Telangiectasias

Abstract: A small-spot size Nd:YAG laser using a pulse width of 20 ms or higher appears to be effective in clearing a significant percentage of facial telangectasias with a single pass. The side effects were minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 19 publications
0
38
0
2
Order By: Relevance
“…Unfortunately, there was no formal quantification of pain levels nor was there any comparison to pain levels when the cryogen spray was not used. A study by Bevin et al 7 used a significantly higher fluence (226–425 J/cm 2 ), using even higher fluencies for smaller vessels. Interestingly, patients were reported to experience only minor pain; however, this was not quantified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there was no formal quantification of pain levels nor was there any comparison to pain levels when the cryogen spray was not used. A study by Bevin et al 7 used a significantly higher fluence (226–425 J/cm 2 ), using even higher fluencies for smaller vessels. Interestingly, patients were reported to experience only minor pain; however, this was not quantified.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Even though noninvasive, patients commonly report significant pain and discomfort when undergoing the treatment. 4,7 …”
mentioning
confidence: 99%
“…Yüzdeki telanjiyektazilerin çoğu kolaylıkla kollabe olan venül kaynaklı dilate damarlar olabilmektedir. Ancak, ala nasi ve burun ucu bölgesindeki telanjiyektaziler nazal arterin lateral dallarıdır ve venüllere kıyasla aynı enerji dozunda daha zor kollabe olduğu için tedaviye daha zor yanıt vermektedir [18][19][20] . Rozase tedavisinde IPL(500-1200nm) etkinliğine dair çalışmalarda hastalarda ortalama 4 seans sonunda %70-80 oranında düzelmeler kaydedilmiştir.…”
Section: Discussionunclassified
“…Srinivas and Kumaresan suggested that the best treatment option for telangiectasias of the lower extremities is achieved with 1064 nm Nd:YAG laser, as its leads to in-depth penetration (5-6 mm), reaching deeply located vessels such as these characterising this particular condition [60] . The use of this laser device was also proposed by other researchers for the treatment of deeper vascular lesions, who also underlined that to avoid overheating of the skin and textural changes, the use of a cooling devise is necessary [61] . The Nd:YAG laser is also a treatment of choice for telangiectasia of darker skin (Fitzpatrick IV-V), as the long wavelength enables deep penetration but minimum absorbance by melanin [62] .…”
Section: Telangiectasiasmentioning
confidence: 99%